Effect of light energy density on conversion degree and hardness of dual-cured resin cement - Komori, P. C P [UNESP]; Paula, A. B.; Martin, A. A.; Tango, R. N. [UNESP]; Sinhoreti, M. A C; Correr-Sobrinho, L. (Operative Dentistry, 2010)
This study evaluated the effect of different light energy densities on conversion degree (CD) and Knoop hardness number (KHN) of RelyX ARC (RLX) resin cement. After manipulation according to the manufacturer's instructions, RLX was inserted into a rubber mold (0.8 mm X 5 mm) and covered with a Mylar strip. The tip of the lightcuring unit (LCU) was positioned in contact with the Mylar surface. Quartz-tungsten-halogen (QTH) and light-emitting diode (LED) LCUs with light densities of 10, 20 and 30 J/cm2 were used to light-cure the specimens. After light curing, the specimens were stored dry in lightproof containers at 37°C. After 24 hours, the CD was analyzed by FT-Raman and, after an additional 24-hours, samples were submitted to Knoop hardness testing. The data of the CD (%) and KHN were submitted to two-way ANOVA and the Tukey's test (α=0.05). QTH and LED were effective light curing units. For QTH, there were no differences among the light energy densities for CD or KHN. For LED, there was a significant reduction in CD with the light energy density set at 10 J/cm2. KHN was not influenced by the lightcuring unit and by its light energy density. © Operative Dentistry.
Keywords: bisphenol A bis(2 hydroxypropyl) ether dimethacrylate; macrogol derivative; polymer; polymethacrylic acid derivative; RelyX ARC; resin; resin cement; chemistry; classification; dental equipment; hardness; human; infrared spectroscopy; light; materials testing; photochemistry; radiation dose; radiation exposure; Raman spectrometry; temperature; time; Bisphenol A-Glycidyl Methacrylate; Composite Resins; Curing Lights, Dental; Hardness; Humans; Light; Materials Testing; Photochemical Processes; Polyethylene Glycols; Polymers; Polymethacrylic Acids; Radiation Dosage; Resin Cements; Spectroscopy, Fourier Transform Infrared; Spectrum Analysis, Raman; Temperature; Time Factors